"Rootbeer" Lucite Bangle Bracelet - Science History Institute (2016)
Amber-tinted lucite bracelet; exterior has raised floral pattern. Lucite methyl methacrylate polymer was among the first plastics derived from petrochemicals. DuPont chemists discovered Lucite in 1931 while exploring the high-pressure technology developed for ammonia production. The polymer's crystal-clear appearance and its strength were far superior to nitrocellulose-based plastics. Lucite was in heavy demand during World War II for use in windshields, nose cones, and gunner turrets for bombers and fighter planes. After the war, DuPont marketed it for use in a variety of decorative and functional uses, such as lamps, hairbrushes, and jewelry.
Keywords: Plastics; Lucite; E.I. du Pont de Nemours & Company